Formulasi Krim Ekstrak Daun Jambu Biji (Psidium guajava L.) dan Avobenzone sebagai Sediaan Tabir Surya - Nurjannah, Siti; Wisudyaningsih, Budipratiwi; Puspitasari, Endah (Journal of Agropharmacy, 2024)
Skin exposed to ultraviolet (UV) rays for a long period of time can cause adverse effects on the skin such as erythema, premature aging and skin cancer so that the use of sunscreen is needed to protect the skin from UV exposure. Sunscreen is used to protect the skin from damage caused by UV exposure by absorbing and scattering UV rays that hit the skin. The study was conducted by making a formulation of guava leaf extract cream and avobenzone in a sunscreen cream preparation, evaluating physical quality, evaluating the in vitro effectiveness of sunscreen preparations including SPF,% TE, and% TP values ​​and data analysis. Sunscreen cream preparations with additional concentrations of guava leaf extract can reduce pH and spreadability, TE and TP but can increase viscosity and SPF values. Formula F3 (7%) has physical quality that meets the criteria of the expected cream preparation and can increase the effectiveness in vitro in sunscreen cream preparations and get the best results with an SPF value of 18.49 ± 1.02 which is included in the ultra protection category and a decrease in the %TE value of 0.486 ± 0.004 and a decrease in %TP of 0.158 ± 0.005 which is included in the total block category. It is recommended in further research to conduct compatibility tests and stability tests of guava leaf extract and avobenzone sunscreen cream preparations.